A first response to osmostress in Acinetobacter baumannii: transient accumulation of K+ and its replacement by compatible solutes. Issue 4 (8th June 2020) - König, Patricia; Averhoff, Beate; Müller, Volker
Summary: The extraordinary desiccation resistance of the opportunistic human pathogen Acinetobacter baumannii is a key to its survival and spread in medical care units. The accumulation of compatible solute such as glutamate, mannitol and trehalose contributes to the desiccation resistance. Here, we have used osmolarity as a tool to study the response of cells to low water activities and studied the role of a potential inorganic osmolyte, K +, in osmostress response. Growth of A. baumannii was K + ‐dependent and the K + ‐dependence increased with the osmolarity of the medium. After an osmotic upshock, cells accumulated K + and K + accumulation increased with the salinity of the medium. K + uptake was reduced in the presence of glycine betaine. The intracellular pools of compatible solutes were dependent on the K + concentration: mannitol and glutamate concentrations increased with increasing K + concentrations whereas trehalose was highest at low K + . After osmotic upshock, cells first accumulated K + followed by synthesis of glutamate; later, mannitol and trehalose synthesis started, accompanied with a decrease of intracellular K + and glutamate. These experiments demonstrate K + uptake as a first response to osmostress in A. baumannii and demonstrate a hierarchy in the time‐dependent accumulation of K + and different organic solutes.